Circ_002664/miR-182–5p/Herpud1 pathway importantly contributes to OGD/R-induced neuronal cell apoptosis. (October 2020) - Liu, Chao; Xu, Xiaohui; Huang, Chao; Zhang, Li; Shang, Dandan; Cai, Weiwei; Wang, Yupeng
Abstract: Objective: Apoptosis is a prominent form of neuron death in cerebral ischemia-reperfusion-induced injury. Accompanied with the pathogenesis, Circ_002664 is upregulated. However, its role in the neuron apoptosis and the underlying mechanisms are unknown. Methods: In this study, HT22 cells were treated with oxygen glucose deprivation and reoxygenation (OGD/R). The cell viability, apoptosis, proliferation and mitochondrial potential were examined. The expressions of interested genes, Circ_002664, miR-182–5p and Herpud1, were measured. The roles of these genes in OGD/R-induced cell injury were investigated by knockdown, overexpression alone or in combination. Additionally, the interactions between Circ_002664, miR-182–5p and Herpud1 were validated by luciferase report assay. The levels of MAP2, CHOP, Cytochrome C (CYC) and cleaved caspase-3 were determined. Results: OGD/R treatment significantly increased cell apoptosis, decreased cell proliferation and mitochondrial potential, as well as increased Circ_002664 and Herpud1 expressions, and decreased miR-182–5p level. Circ_002664 knockdown markedly inhibited the effects by OGD/R on cell survival and altered expression of miR-182–5p and Herpud1. MiR-182–5p was observed sponged by Circ_002664 and negatively mediated its effect above mentioned, and this was by directly targeting Herpud1. Additionally, it was observed that CHOP expressions were regulated by Circ_002664/miR-182–5p/Herpud1 pathway, and in turn mediated its regulation in CYC and cleaved caspase-3. Conclusions: In summary, our data showed that the Circ_002664 importantly contributed to neuronal cell apoptosis induced by OGD/R treatment, and this might be achieved by directly targeting miR-182–5p/Herpud1 pathway. Highlights: Circ_002664 significantly increased in neuronal cells after OGD/R treatment. Circ_002664 acted as a sponge of miR-182–5p. miR-182–5p directly targeted Herpud1 and negative regulate its expression. Circ_002664/miR-182–5p/Herpud1 regulated expressions of CHOP and MAP2. Circ_002664/miR-182–5p/Herpud1 was associated with neuronal cell injury after OGD/R.